Dynamic carboxymethyl chitosan-based nano-prodrugs precisely mediate robust synergistic chemotherapy. (1st September 2022) - Wang, Zhexiang; Wang, Di; Liu, Xin; Wu, Haifang; Liu, Yuqing; Ge, Yang; Yan, Guoqing; Tang, Rupei
Abstract: Currently, the polysaccharide-based nano-prodrug crosslinked by stimuli-responsive synergetic prodrug is of great demand, owing to its excellent stability, synergetic effect and tumor selectivity, and circumventing the dilemma of dose-limiting toxicity and immunogenicity induced by that crosslinked or grafted via a single drug. Herein, the dynamic carboxymethyl chitosan (CMCS)-based nano-prodrugs with precise structure were facilely fabricated, via crosslinking reaction between CMCS and water-soluble synergistic small molecule prodrug (cisplatin-demethylcantharidin conjugate) and further stabilization by glutaraldehyde. The pH/glutathione (GSH)-responsive double-crosslinked structure endowed the nano-prodrugs with long-term storge and circulation stability at physiological pH, and dynamic transitions at tumor sites including extracellular surface amino protonation and intracellular efficient drug release, which promoted selective tumor accumulation and synergistic cytotoxicity, therefore achieving robust tumor suppression while decreasing side effects. Thus, the dynamic precise CMCS-based nano-prodrugs crosslinked by water-soluble synergistic prodrug have great potential for highly selective robust chemotherapy attractive for clinical translation. Graphical abstract: Unlabelled Image